Is the atrophic phenotype of tibiofemoral osteoarthritis associated with faster progression of disease? The MOST study. Issue 10 (October 2017) - Crema, M.D.; Felson, D.T.; Guermazi, A.; Nevitt, M.C.; Niu, J.; Lynch, J.A.; Marra, M.D.; Torner, J.; Lewis, C.E.; Roemer, F.W.
Summary: Objective: To assess the associations of atrophic tibiofemoral osteoarthritis (OA) with progression of radiographic joint space narrowing (JSN) and magnetic resonance imaging (MRI)-defined progression of cartilage damage. Design: Participants of the Multicenter Osteoarthritis (MOST) Study with available radiographic and MRI assessments at baseline and 30 months were included. The atrophic OA phenotype was defined as Osteoarthritis Research Society International (OARSI) grades 1 or 2 for JSN and grade 0 for osteophytes. Based on MRI, atrophic OA was defined as tibiofemoral (TF) cartilage damage grades ≥3 in at least 2 of 10 subregions with absent or tiny osteophytes in all TF subregions. Progression of JSN and cartilage loss on MRI, was defined as (1) no, (2) slow, and (3) fast progression. Co-variance and logistic regression with generalized estimated equations were performed to assess the association of atrophic knee OA with any progression, compared to non-atrophic OA knees. Results: A total of 476 knees from 432 participants were included. There were 50 (10.5%) knees with atrophic OA using the radiographic definition, and 16 (3.4%) knees with atrophic OA using MRI definition. Non-atrophic OA knees more commonly exhibited fast progression of JSN and cartilage damage. Logistic regression showed that the atrophic phenotype of knee OA was associated with a decreased likelihood of progression of JSN and cartilage loss. Conclusion: In this sample, the atrophic phenotype of knee OA was associated with a decreased likelihood of progression of JSN and cartilage loss compared to the non-atrophic knee OA phenotype.